Extraction and partial purification for adhesive protein FimH from type-1 pili which isolated from uorpathogenic E.coli (Baghdad Science Journal, 2025)
Type-1 fimbriae have been extracted from E.coli which was previously isolated, the yield was 2.8 mg fimbriae/10 g bacteria , the crude fimbriae was partially purified by several solubilization and recrystilization methods using a series of buffer and solutions to decrease the impurities, the yield of fimbriae from all these steps was 2.1 mg fimbriae / 10 g bacteria. Adhesive protein FimH was extracted from fimbriae by separation then partially purified by Gel-chromatography sephadex G-100, the yield of FimH was 250 µg/ml, while fimbriae protein was 50.6 µg/ml. The partially purified FimH revealed one clear band in SDS-PAGE, as well as protein fimbriae with molecular weight (28300,17500) Dalton respectively, when compared with standard protein curve.